(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This article examines and evaluates the effectiveness of project management on crisis management in construction projects. In this article, the role and importance of project management and crisis management in construction projects have been examined in detail. First, the role and importance of project management in construction projects have been explained. Project management includes planning, setting resources, controlling costs, and scheduling, which helps to achieve desired results within the time frame and budget. Also, the principles and techniques of project management have been shown to improve project performance, reduce errors, and increase the satisfaction of the organizer and other stakeholders. Then, the role and importance of crisis management in construction projects have been investigated. Crisis management includes identifying and analyzing risks, designing and implementing emergency plans, and controlling and resolving the consequences of accidents. The statistical population of this research includes 180 personnel working in the construction projects offices of General Mechanics Company. Considering the characteristics of the statistical population and the small number and availability of all members, a simple random sampling method was chosen. The reliability of the questionnaire was obtained using Cronbach’s alpha coefficient of 0.96 for the crisis management standards questionnaire and 0.97 for project management achievements. We accept the distribution status of the variables using the Kolomogrov and Smirnov tests, which were all normal based on the main hypothesis that project management and crisis management have a meaningful relationship, and based on the results, only the impact of planning dimension and control dimension of communication management on crisis management is significant. And only after project management planning has an impact on crisis management. Finally, the effectiveness of project management on crisis management in construction projects has been discussed. According to the analysis of data and reports, the results have shown that improvement in project management leads to significant improvement in crisis management. This improvement includes reducing the probability of accidents.